Mindfulness and self-regulation strategies predict performance of Romanian handball players - Popa, D.; Mîndrescu, V.; Iconomescu, T.-M.; Talaghir, L.-G. (Sustainability, 2017)
Previous studies on handball players` performance are focused more on influence of physical, physiological factors and tactical strategies and less on the influence of cognitive, metacognitive and attentional regulation strategies. Performance can be achieved by attentional and emotional regulation alongside cognitive, metacognitive and procedural regulation strategies. This study explores the association between self-regulation strategies, mindfulness practice and performance. The sample consists of 288 Romanian handball players. The participants were 30% male and 70% female, with age between 12.01 and 14 years old, divided in three categories. The quantitative research design is descriptive and transversal. The method was survey based on questionnaires. There were interesting results found in different age categories and different performance levels. The variables (state mindfulness of body, self-monitoring, and self-efficacy) explained 87% of the variance in sports performance, in a hierarchical multiple regression. The research findings indicated that handball players with a high level of acceptance of one`s own thoughts and emotions, non-judging present-moment awareness, conscious monitoring the execution of movements, and confidence in their abilities to succeed could have more chances to achieve the desired performance.